Knowledge Sharing Strategy and Emission Reduction Benefits of Low Carbon Technology Collaborative Innovation in the Green Supply Chain - Wang, Fuqiang; Li, Huimin; Cao, Yongchao; Zhang, Chengyi; Ran, Yunlong (Frontiers in Environmental Science, 2022)
Knowledge sharing (KS) in the green supply chain (GSC) is jointly determined by the KS efforts of suppliers and manufacturers. This study uses the differential game method to explore the dynamic strategy of KS and the benefits of emission reduction in the process of low carbon (LC) technology in the GSC. The optimal trajectory of the knowledge stock and emission reduction benefits of suppliers and manufacturers under different strategies are obtained. The validity of the model and the results are verified by numerical simulation analysis, and the sensitivity analysis of the main parameters in the case of collaborative sharing is carried out. The results show that, firstly, in the centralized decision-making situation, the KS effort between suppliers and manufacturers is relatively high. Moreover, GSC's knowledge stock and emission reduction benefits are also higher than those of non-cooperation. Secondly, the cost-sharing mechanism can increase the knowledge stock and emission reduction benefits of the GSC, and realize the Pareto improvement of the knowledge stock and emission reduction benefits. However, the cost-sharing mechanism can only increase the supplier's KS effort, and has no incentive effect on the manufacturer's KS effort. Thirdly, it is found that carbon price and knowledge decay rate are the main factors affecting KS. The study provides a theoretical basis for promoting KS in the GSC and LC technology innovation.